Process development for the synthesis of saturated branched fatty derivatives: Combination of homogeneous and heterogeneous catalysis in miniplant scale. (2nd April 2016) - Haßelberg, J.; Behr, A.; Weiser, C.; Bially, J.B.; Sinev, I.
Abstract: Saturated branched fatty derivatives find application in lubricant and cosmetic industry due to the decisive advantages in temperature and viscosity behavior compared to their linear homologs. Thus, finding new synthesis routes, particularly based on renewable resources, is of great industrial interest. This work covers a new synthesis route for production of such saturated branched derivatives based on linoleic methyl ester. The developed process combines homogeneously rhodium catalyzed co-oligomerization of linoleic methyl ester with ethylene and heterogeneously catalyzed hydrogenation of the co-oligomers in miniplant scale. The paper focuses on the hydrogenation in trickle bed reactor and optimization of operation conditions as well as optimization of packings and liquid distribution. Saturated branched derivatives with very low iodine values have been produced in miniplant scale using a diluted catalyst packing consisting of large Pd/C catalyst pellets and small SiC particles. Different SiC fractions have been tested to investigate the effect on liquid distribution. Additionally long term stability of the heterogeneous Pd/C catalyst has been successfully tested for more than 100 h. Simultaneous adsorption of the used homogenous rhodium catalyst on the fixed bed was analyzed by XPS. Additionally this paper discusses the general transferability of the process combination consisting of homogeneous and heterogeneous reaction steps to other synthesis route and product groups. Graphical abstract: Saturated branched fatty derivatives are interesting products for the lubricant and cosmetics industry. The described process combines the homogeneously rhodium catalyzed co-oligomerization of fatty acid methyl esters and ethene with further heterogeneously catalyzed hydrogenation. This paper focusses on the hydrogenation in a trickle bed reactor and presents experimental investigations on operation conditions as well as optimization of packings and liquid distribution. Highlights: Process with consecutive combination of homo- and heterogeneous catalysis. Synthesis of saturated branched fatty derivatives from renewable resources. Optimization of liquid distribution by packing dilution with SiC. Long-term stability of heterogeneous Pd-catalyst successfully tested (>100 h). No palladium leaching to liquid phase observed.